2015
DOI: 10.1093/ndt/gfv214
|View full text |Cite
|
Sign up to set email alerts
|

Recipient obesity and outcomes after kidney transplantation: a systematic review and meta-analysis

Abstract: Despite having a much higher likelihood of DGF, obese transplant recipients have only a slightly increased risk of graft loss and experience similar survival to recipients with normal BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 55 publications
6
120
1
2
Order By: Relevance
“…In the same study, the meta‐analysis of studies using fully adjusted regression analysis (rather than an absolute risk ratio) demonstrated no association between obesity and mortality after kidney transplantation (HR 1.10; 95% CI 0.89‐1.15). This finding concurred with that of Hill et al, who used a similar methodology (HR 1.24; 95%CI 0.9‐1.7) . All of these reviews have suggested that factors associated with obesity, rather than obesity per se, that explain the differences between studies that have adjusted for potential confounders and those which have not.…”
Section: Obesity and Kidney Transplant Outcomessupporting
confidence: 83%
“…In the same study, the meta‐analysis of studies using fully adjusted regression analysis (rather than an absolute risk ratio) demonstrated no association between obesity and mortality after kidney transplantation (HR 1.10; 95% CI 0.89‐1.15). This finding concurred with that of Hill et al, who used a similar methodology (HR 1.24; 95%CI 0.9‐1.7) . All of these reviews have suggested that factors associated with obesity, rather than obesity per se, that explain the differences between studies that have adjusted for potential confounders and those which have not.…”
Section: Obesity and Kidney Transplant Outcomessupporting
confidence: 83%
“…These trends were observed in both the AD and LDs categories. Obese donor BMI has been shown to increase the risk of DGF, [15] while another study showed that there was little influence on transplant outcomes unless donor BMI was greater than 45 kg/m. 2 In our model, we adjusted for donor BMI and still found that recipient BMI had an independent impact on outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of survival, obese patients tend to have no decrease in short-term survival but may have attenuated overall survival; however, whether this is related to a decrease in graft function or other obesity-related effects is undetermined (27,33). In terms of graft survival, acute rejection tends to be increased in obese patients (27,34,37), and obesity is associated with delayed graft function in kidney transplantation (29)(30)(31)(32), hepatocellular carcinoma in liver transplants (27,33), and grade III primary graft dysfunction in lung transplants (27).…”
Section: How Does Obesity Affect Solid Organ Transplantation?mentioning
confidence: 99%